Do Malassezia yeasts colonize the guts of people living with HIV? - Abdourahim Abdillah; Isabelle Ravaux; Saadia Mokhtari; Stéphane Ranque (PLoS ONE, 2025)
Malassezia yeasts are commensals of human skin. In contrast to culture-based studies, metagenomic studies have detected abundant Malassezia reads in the gut, especially in patients living with HIV. Whether Malassezia colonizes and persists in the gut remains an open question. This study aimed to describe the influence of HIV-associated immunodeficiency on gut colonization by Malassezia and to assess whether Malassezia are alive. Stool samples were prospectively collected over one–five visits from ten controls and 23 patients living with HIV (10 had CD4 < 200/mm3 and 13 had CD4 > 500/mm3). Each sample was cultured and subjected to Malassezia viability PCR and both fungal and bacterial metabarcoding. Abundant M. furfur colonies were cultured from an HIV-immunocompromised patient. M. furfur and M. globosa were isolated in very low quantities from healthy volunteers. Viability Malassezia-specific qPCR was positive in three HIV-immunocompromised patients. Metagenomic analyses showed that Malassezia reads were significantly more abundant in immunocompromised patients living with HIV and erratic over time in all participants. Our findings emphasise that Malassezia are rarely cultured from human stool samples, despite the use of specific culture media. Although HIV-related immunosuppression appears to be associated with the presence of Malassezia, these yeasts do not persist and colonise the gut, even in immunocompromised patients.